EKSPLORASI SERTA IDENTIFIKASI BAKTERI DAN CENDAWAN TANAH KABUPATEN SAMPANG SEBAGAI AGENS HAYATI DI LABORATORIUM AGENS HAYATI UPT PTPH JAWA TIMUR - Dyah Putri Yudha Yanti; Misnati Nur Indahsari, Wiwin (Jurnal Biogenerasi, 2026)
Exploration of soil microorganisms as biological control agents is one of the environmentally friendly approaches to controlling plant pests and diseases. This study aimed to explore and identify soil bacteria and fungi with potential as biological control agents at the Biological Control Laboratory of the Technical Implementation Unit for Food Crops and Horticultural Plant Protection, East Java. The research was conducted from January to April 2025 through bacterial isolation using the serial dilution method and fungal isolation using the baiting method, followed by macroscopic and microscopic observations as well as physiological and biochemical tests. The results showed that two soil bacterial isolates were obtained, in which one isolate was suspected to be Bacillus sp. with potential as a biological control agent, while the other isolate showed no potential as a biological control agent. A bacterial isolate initially suspected as Bacillus thuringiensis was not identified as an entomopathogenic bacterium based on physiological and biochemical tests. Fungal exploration resulted in isolates suspected as Trichoderma sp. and Aspergillus sp